2007
DOI: 10.1210/jc.2006-1705
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Lipoprotein Phenotype and Low-Density Lipoproteins Size and Subclasses in Women with Polycystic Ovary Syndrome

Abstract: Increase of type III or type IV LDL subclasses is a common finding in PCOS and represents the second most common lipid alteration after HDL-cholesterol decrease. However, in our PCOS patients, because of relatively low triglyceride levels, complete ALP is uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 31 publications
9
61
0
1
Order By: Relevance
“…In females, changes in fat distribution coincide with the onset of ovarian production of estrogen and progesterone during puberty (15)(16)(17)(18)(19) and with cessation of hormone production during menopause (20)(21)(22). Marked changes in female lipid metabolism occur during pregnancy (23,24) and in reproductive disorders accompanied with hormonal changes (25).…”
Section: Introductionmentioning
confidence: 99%
“…In females, changes in fat distribution coincide with the onset of ovarian production of estrogen and progesterone during puberty (15)(16)(17)(18)(19) and with cessation of hormone production during menopause (20)(21)(22). Marked changes in female lipid metabolism occur during pregnancy (23,24) and in reproductive disorders accompanied with hormonal changes (25).…”
Section: Introductionmentioning
confidence: 99%
“…Early investigations reported a more than twofold higher prevalence of the type B lipid profile in patients with type 2 diabetes mellitus (52 % of patients vs. 24 % in the control group) [31]. This association was also shown in women with gestational diabetes mellitus who presented with a decreased LDL particle size when compared with normoglycemic women [32], as well as in women with another state of increased insulin resistance, the polycystic ovary syndrome [33,34]. Studies investigating insulin resistance with the hyperinsulinemic clamp technique could show that progressive insulin resistance was associated with a decrease in LDL size as a result of a marked increase in small LDL particles.…”
Section: Small Ldl Particles and Type 2 Diabetes Mellitusmentioning
confidence: 93%
“…Dyslipidemia usually include low HDL-cholesterol levels and elevated triglyceride concentrations while increased LDL and total cholesterol have been also found but with a lower prevalence (14). Beyond plasma lipids, women with PCOS have lower LDL size due to 5 increased levels of atherogenic small, dense LDL [16][17][18] and recent studies have suggested the "quality" and not only the "quantity" of LDL is strongly associated with cardiovascular risk (19).…”
Section: Markers Of Cardiovascular Risk In Pcosmentioning
confidence: 99%